Critical analysis of the concept of de facto statelessness - Fuentes, Juan (2020)
This article studies the definition of de iure statelessness contained in article 1, (1) of the Convention Relating to the Status of Stateless Persons (1954) and criticizes the UNHCR’S concept of de facto statelessness.